Determinantes da demanda por exame preventivo de câncer de próstata no Brasil e em suas regiões. - Carvalho, Fabrícia Jóisse Vitorino (2016)
Prostate cancer is one of the most common tumors in the male population. Causes premature deaths and costs the family, the public health system and the whole society. In this context, this study aims to analyze the determinants of demand for preventive screening for prostate cancer in Brazil and its Regions. From the information of the National Health Research (PNS, 2013), it was organized that study, characterized by men over 40, who answered the question about the digital rectal examination (RT) that were at least once the physician. It is worth noting that the last cut was made in order to resolve the bias related to access to health services. Analysis of the data indicates that over 50% of Brazilian men never performed the screening test for prostate cancer. The main reasons cited for not performing were the lack of guidance, not find it necessary, and shame. The three described allegations indicate the existence disinformation and disbelief to the prevention of disease. Furthermore, with the estimation of the logit model orderly partial proportional odds, it was concluded that it is not the lack of access to health services, but the level of education and access to information that determines the demand for preventive examination prostate cancer. Thus, it is necessary to resolve the deficit of knowledge about the tumor, so that you can increase the early diagnosis of that cancer.